Evaluating an organizational innovation: evidence from the conglomerate merger wave. (18th June 2021) - Klein, Peter; Wuebker, Robert; Chen, Mo; Zoeller, Kathrin
Abstract: How do we assess new forms of economic organization? As with other innovations, the value of a new organizational form is initially unknown. When assets are traded in financial markets, the information embodied in prices represent one mechanism through which organizational innovations are evaluated. We apply an experimental-learning framework to explore the influence of the capital markets on economic organization, using the conglomerate merger wave of the 1960s and 1970s as an empirical context. In our setting, the initial market popularity of conglomerates, followed by their rapid decline, is indicative of investors attempting to determine the value of a new organizational form. We provide event-study evidence that investors systematically updated their beliefs about the value of the conglomerate form based on new information (positive or negative) about the largest and most newsworthy conglomerates. Our results suggest that financial market participants make judgments not only about specific companies, but about organizational structure itself.